Evaluating the Efficiency of Indonesian Library and Information Science Journals: A Data Envelopment and Bibliometric Analysis - Ansar, Fadli; Ibrahim, Cecep; Jaya, Asrul; Fadhli, Rahmat; Umasugi, Mohbir (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
This study evaluates the efficiency of Indonesian Library and Information Science journals indexed by SINTA by applying Data Envelopment Analysis (DEA) using a Variable Return to Scale (VRS) model. The primary aim is to assess the performance of these journals to identify areas of strength and inefficiency. The study encompasses twenty-one journals, which served as decision-making units (DMUs). The input variables considered include Article Processing Charges (APC), Editorial Team, Number of Authors, and Number of Publications, while the output variables were Number of Citations and H5-Index. Data were collected from journal websites and the Sinta database covering 2018 to 2022. The analysis was conducted using MaxDEA software. An efficiency score of 1 indicated an efficient journal, whereas scores below 1 denoted inefficiency. The study reveals six journals as efficient: Jurnal Kajian Informasi & Perpustakaan, Khizanah Al-Hikmah: Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, IQRA': Jurnal Perpustakaan dan Informasi, Bibliotech: Jurnal Ilmu Perpustakaan dan Informasi, PUBLIS (Publication Library and Information Science), and Imam Bonjol Journal: Kajian Ilmu Informasi dan Perpustakaan. However, most journals were found to be inefficient, with an average efficiency score of 0.809. These findings are significant as they provide valuable insights for journal editors and policymakers. The results offer guidance on optimizing resource allocation and developing strategies to enhance the quality and impact of scholarly publications within the Library and Information Science field.